2017
DOI: 10.1093/sleep/zsx108
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Follow-Up Comparing Cognitive Behavioral Therapy for Depression to Cognitive Behavioral Therapy for Insomnia, for Patients With Both Diagnoses

Abstract: This 3-year follow-up compared insomnia treatment to depression treatment for patients with both diagnoses. Forty-three participants were randomized to either treatment, in the form of Internet-delivered therapist-guided cognitive behavior therapy (CBT), and 37 (86%) participants provided primary outcome data at the 3-year follow-up. After 3 years, reductions on depression severity were similar in both groups (between-group effect size, d = 0.33, p = .45), while the insomnia treatment had superior effects on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 38 publications
(37 reference statements)
1
57
1
2
Order By: Relevance
“…At a significance threshold of α = 0.05, this sample size provides a power 1-β = 0.80, the minimal detectable interaction effect is d = 0.5, while the minimal detectable main effects of either CBT-I or CT are d = 0.44 (medium). A previous similar study reported a more than medium effect of CBT-I on depressive symptoms at T1 (d = 0.74) up to a large effect at T4 (d = 1.12) [63].…”
Section: Sample Size Calculationmentioning
confidence: 61%
See 1 more Smart Citation
“…At a significance threshold of α = 0.05, this sample size provides a power 1-β = 0.80, the minimal detectable interaction effect is d = 0.5, while the minimal detectable main effects of either CBT-I or CT are d = 0.44 (medium). A previous similar study reported a more than medium effect of CBT-I on depressive symptoms at T1 (d = 0.74) up to a large effect at T4 (d = 1.12) [63].…”
Section: Sample Size Calculationmentioning
confidence: 61%
“…Other studies have shown similar results confirming that CBT-I is effective in reducing both insomnia and depressive symptoms [29,30] and can even prevent a depressive episode at 1 year follow up [31]. Interestingly, a study comparing CBT for insomnia and CBT for depression in comorbid insomnia and depression patients, found that CBT for insomnia was equally effective in reducing depression severity compared with CBT for depression, while more effective in reducing insomnia complaints [32,33]. Light therapy, probably the strongest of the different CTs, has also demonstrated to ameliorate depressive symptoms not only in patients suffering from seasonal affective disorder, but also in patients with non-seasonal depression [34].…”
mentioning
confidence: 70%
“…Moreover, insomnia has a high comorbidity with depression, and the two conditions share some of the neurobiological markers, making the quest for identifying stimulation targets even more important. Most importantly, PI is no longer considered a secondary condition to depression but rather an independent clinical entity; while insomnia is a risk factor for depression onset [ 56 , 57 ], depression treatments are not a sufficient remedy for insomnia [ 58 ]. Even further, it seems that insomnia-targeted cognitive behavioral therapy (CBT) might be a better therapeutic approach to cure both insomnia and depression than CBT based on depression symptoms: a randomized trial comparing the efficacy of CBT for insomnia and depression (tested in separate groups of patients with both diagnoses) have shown insomnia treatment inducing more beneficial effects than depression treatment, in both conditions [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an RCT examining Internet-based CBT for depression, 80% of participants reported satisfaction towards the treatment received, and 74% of participants felt the program was equal to or better than a "real" therapist [17]. Similarly, Internet-based self-help CBT-I is found to significantly reduce both insomnia and depression severity [18]. The effects of internet-based CBT-I on improving insomnia severity, sleep quality, and depression have been supported by multiple meta analyses (e.g., [19][20][21]).…”
Section: Introductionmentioning
confidence: 99%